MOTIVATIONS OF VENEZUELAN RECENT IMMIGRATION TO ARGENTINA. THE CASE OF SANTA ROSA-TOAY, LA PAMPA, ARGENTINA - Dolores Linares, María (2020)
This article’s objective is to analyze the motivations of recent migrants from Venezuelato begin their migration trajectories towards Argentina between 2019 and 2019. Throughthe review of specialized literature, national and local statistics and in-depth interviewsconducted with 15 Venezuelan migrants in Santa Rosa-Toay (La Pampa), we are interestedin determine whether it is a forced or voluntary migration. Conceptually, the categories ofexile, refuge (right of asylum) and diaspora will be discussed to propose, as a hypothesis, that the notion of migration due to privation (Cozzani de Palmada, 2005) allows theincorporation of both voluntary and non-voluntary characteristics to describe theVenezuelan migration in our study area.